Meningkatkan kepatuhan wajib pajak kendaraan bermotor di Kabupaten Pati: Peran kesadaran, sanksi, sosialisasi, dan kualitas pelayanan - Amalia, Azka; Budiantoro, Risanda (Journal of Accounting and Digital Finance, 2025)
Motor vehicle tax is a strategic source of regional revenue; however, taxpayer compliance remains a persistent challenge. This study aims to analyze the influence of taxpayer awareness, tax sanctions, tax socialization, and service quality on motor vehicle taxpayer compliance in Pati Regency. Data were collected through a questionnaire survey involving 100 respondents selected via accidental sampling. The analysis was conducted using multiple linear regression. The findings indicate that all independent variables have a positive and significant effect on compliance. These results underscore that enhanced awareness, effective enforcement of sanctions, intensified outreach, and optimal public service are key factors in determining tax compliance. This study provides empirical evidence to inform local fiscal strategies tailored to the characteristics of taxpayers. Policy implications underscore the need for an integrated approach that combines educational and preventive measures, supported by technological innovations in tax services. Strengthening compliance is expected to optimize local revenue and support infrastructure development, as well as improve public service delivery.